Psychometric performance of the brazilian version of the Mini-cuestionario de calidad de vida en la hipertensión arterial (MINICHAL) (Revista Latino-Americana de Enfermagem, 2011)
This study aimed to evaluate the feasibility, acceptability, ceiling and floor effects, reliability, and convergent construct validity of the Brazilian version of the Mini Cuestionario de Calidad de Vida en la Hipertensión Arterial (MINICHAL). The study included 200 hypertensive outpatients in a university hospital and a primary healthcare unit. The MINICHAL was applied in 3.0 (± 1.0) minutes with 100% of the items answered. A "ceiling effect" was observed in both dimensions and in the total score, as well as evidence of measurement stability (ICC=0.74). The convergent validity was confirmed by significant positive correlations between similar dimensions of the MINICHAL and the SF-36, and significant negative correlations with the Minnesota Living with Heart Failure Questionnaire - MLHFQ, however, correlations between dissimilar constructs were also observed. It was concluded that the Brazilian version of the MINICHAL presents evidence of reliability and validity when applied to hypertensive outpatients